2011
DOI: 10.1103/physrevlett.106.017002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Two Andreev-Like Energy Scales inLa2xSrxCuO4Superconductor–Normal-Metal–Superconductor Junctions

Abstract: Conductance spectra measurements of highly transparent ramp-type junctions made of superconducting La 2−x Sr x CuO 4 electrodes and non superconducting La 1.65 Sr 0.35 CuO 4 barrier are reported. At low temperatures below T c , these junctions have two prominent Andreev-like conductance peaks with clear steps at energies ∆ 1 and ∆ 2 with ∆ 2 > 2∆ 1 . No such peaks appear above T c . The doping dependence at 2 K shows that both ∆ 1 and ∆ 2 scale roughly as T c . ∆ 1 is identified as the superconducting energy g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(63 reference statements)
4
1
0
1
Order By: Relevance
“…Although reminiscent of the pseudogap T * behavior as depicted from ARPES measurements by the dotted line31, the slopes of the two lines are very different, possibly indicating the presence of additional effects such as phase fluctuations or that the two phenomena are unrelated2021. Similar phase diagram trends were observed before in the cuprates in Nernst effect measurements32, in high magnetic field results33, in infrared and terahertz spectroscopy1734, and in higher energy gap results obtained in Andreev conductance spectroscopy measurements35. These previous results, as well as the new one presented here, provide additional support for strong superconducting fluctuation effects and the preformed pairs scenario in the underdoped regime of the cuprates above T c , but not necessarily up to the T * transition-line of the pseudogap.…”
Section: Discussionsupporting
confidence: 70%
“…Although reminiscent of the pseudogap T * behavior as depicted from ARPES measurements by the dotted line31, the slopes of the two lines are very different, possibly indicating the presence of additional effects such as phase fluctuations or that the two phenomena are unrelated2021. Similar phase diagram trends were observed before in the cuprates in Nernst effect measurements32, in high magnetic field results33, in infrared and terahertz spectroscopy1734, and in higher energy gap results obtained in Andreev conductance spectroscopy measurements35. These previous results, as well as the new one presented here, provide additional support for strong superconducting fluctuation effects and the preformed pairs scenario in the underdoped regime of the cuprates above T c , but not necessarily up to the T * transition-line of the pseudogap.…”
Section: Discussionsupporting
confidence: 70%
“…The resistance spread above the transition can be due to thickness variations over the 10 mm width of the wafer. Similar but smaller spreads however, were also observed in our previous studies of all-epitaxial cuprate ramp junctions [12,13]. Thus the obviously non-epitaxial nature of the present junctions (hexagonal Bi 2 Se 3 on cubic NbN or STO can never be epitaxial) can also contribute to the large spread of the junctions properties.…”
Section: Resultssupporting
confidence: 88%
“…We note however, that PITS could be at the origin of previous results where a small supercurrents of 5 kA/cm 2 at 4 K had been observed in similar SFS junctions but with Y Ba 2 Cu 3 O 7−δ electrodes and a 20 nm thick La 0.67 Sr 0.33 MnO 3 barrier [10]. Following our recent study of similar SNS junctions but with a normal La 1.65 Sr 0.35 CuO 4 barrier where two Andreev-like energy scales were observed [11], in the present study we concentrated on low biases and observed only the lower superconducting energy scale. The negative magnetoresistance of the LCMO barrier at 2 K had also been detected in the conductance spectra of the present work, either under a high magnetic field in the superparamagnetic state of the LCMO barrier or after field cycling.…”
supporting
confidence: 62%
“…This means that our preparation process is quite clean and introduces only a negligible amount of contamination at the interfaces of our junctions. In passing we note that in the supplementary material of a previous publication by our group concerning these short junctions [11], the given J c (2K) values were in error and the correct values are given here.…”
mentioning
confidence: 77%